Factors associated with consultation rates in general practice in England, 2013-14 - Mukhtar, T; Bankhead, C; Stevens, S; Perera, R; Holt, T; Salisbury, C; Hobbs, F (Royal College of General Practitioners, 2018)
Background Workload in general practice has risen during the last decade, but the factors associated with this increase are unclear. Aim To examine factors associated with consultation rates in general practice. Design and setting A cross-sectional study. A sample of 304,937 patients registered at 316 English practices between 2013 and 2014 was drawn from the Clinical Practice Research Datalink. Method We linked age, sex, ethnicity, smoking status, and deprivation measures with practice level data on staffing, rurality, training practice status, and Quality and Outcomes Framework performance. We conducted multilevel analyses of patient consultation rates. Results Consultations were grouped into three types: General practitioner or nurse (All), general practitioner (GP), and nurse. Non-smokers consulted less than current smokers (All: RR=0.88, 95% CI: 0.87 to 0.89; GP: 0.88 [0.87 to 0.89]; nurse: 0.91 [0.90 to 0.92]. Consultation rates were higher for those in the most deprived quintile compared to the least deprived quintile (All: 1.18 [1.16 to 1.19]; GP: 1.17 [1.15 to 1.19]; nurse: 1.13 [1.11 to 1.15]. For all three consultation types, consultation rates increased with age, female sex, and varied by ethnicity. Rates in practices with between >8 and <=19 full time equivalent (FTE) GPs were higher compared to those with <=2 FTE GPs (All: 1.26 [1.06 to 1.49]; GP: 1.36 [1.19 to 1.56]). Conclusions Our analyses show consistent trends in factors related to consultation rates in general practice across three types of consultation. These data can be used inform the development of more sophisticated staffing models, and resource allocation formulae.